2016
DOI: 10.1002/cphc.201600265
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Methyl Torsional Barriers of the E and Z Isomers of Butadienyl Acetate by Microwave Spectroscopy

Abstract: The Fourier transform microwave spectra of the E and Z isomers of butadienyl acetate were measured in the frequency range from 2 to 26.5 GHz under molecular-jet conditions. The most stable conformer of each isomer, in which all heavy atoms are located in a symmetry plane, was identified after analyzing the spectrum by comparison with the results from quantum-chemical calculations. The barriers to internal rotation of the acetyl methyl group were found to be 149.1822(20) and 150.2128(48) cm(-1) for the E and Z … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 23 publications
4
43
0
Order By: Relevance
“…It is interesting to compare the V 3 potential of the ring methyl group in OMA with those of other toluene derivatives, where the substituents are also in the ortho position with respect to each other (see Table ). In the case of acetates, we found that both the steric and electronic effects might affect the methyl barrier height, where the electronic effect has a larger influence than the steric effect . In the case of ortho substituted toluene, the influence of the substituent on the barrier height seems to be predominantly of a steric nature.…”
Section: Figurementioning
confidence: 79%
See 1 more Smart Citation
“…It is interesting to compare the V 3 potential of the ring methyl group in OMA with those of other toluene derivatives, where the substituents are also in the ortho position with respect to each other (see Table ). In the case of acetates, we found that both the steric and electronic effects might affect the methyl barrier height, where the electronic effect has a larger influence than the steric effect . In the case of ortho substituted toluene, the influence of the substituent on the barrier height seems to be predominantly of a steric nature.…”
Section: Figurementioning
confidence: 79%
“…In the case of acetates, we found that both the steric and electronic effectsm ight affect the methylb arrier height, where the electronic effect has al arger influence than the sterice ffect. [22] In the case of ortho substituted toluene, the influence of the substituent on the barrierh eights eems to be predominantly of as teric nature. Small or slim substituents such as fluorinea toms (in o-fluorotoluene [23] or 2,4-difluorotoluene [4] )o rc yano groups (o-tolunitrile [24] )h indert he internal rotationm uch lesst han voluminous chlorine atoms (o-chlorotoluene [25] ), hydroxyl groups (ocresol [6] ), methyl groups (o-xylene [26] or 3,4-dimethylbenzaldehyde [27] ), methoxyg roups (OMA), or aldehyde groups (2,5-dimethylbenzaldehyde [27] ).…”
mentioning
confidence: 99%
“…[15][16][17][18][19][20][21] This behavior in ketones,w hereby the substituent on the other side of the carbonyl group causes the acetyl-methyl barrier to vary over aw ider ange without any apparent trends, is in strong contrast to acetates, which can be divided into classes with predictable barrier heights. [22] For example in a,b-saturated alkyl acetates,t he barrier to internal rotationi sa pproximately 100 cm À1 and remains largely invariant. [23,24] This value cannotb ee asily predicted when an electronic effect exists, for example, due to the presence of double bondso rl one electron pairs, which can contributei n aconjugated system.…”
Section: Resultsmentioning
confidence: 99%
“…The sterical hindrance between the methoxy and the o-methyl group is the main reason for this intermediate value of V 3 , which has been confirmed by the results obtained for a number of osubstituted toluenes. [31] and [32]. [4] However, in 23DMA the intermediate barrier of about 519 cm À1 of the m-methyl group is not surprising because the adjacent o-methyl group causes sterical hindrance.…”
Section: Discussionmentioning
confidence: 99%
“…The very low barrier of the o-methyl group can be explained in a similar way as has been described in Refs. [31] and [32]. If we assume that the methoxy methyl group and the two other methyl groups are similar, then the o-methyl group, which has a C 3v symmetry, experiences potentials based on a C 2v frame symmetry as in toluene CH 3 ÀC 6 H 5 (V 6 = 4.8 cm À1 ) [33] or nitromethane CH 3 NO 2 (V 6 = 4.9 cm À1 ), [34] where only a V 6 term but no V 3 contribution exists.…”
Section: Discussionmentioning
confidence: 99%